(untitled) (Revista Científica Tecnológica - ISSN: 2708-7093, 2020)
In this article the peasant and indigenous movements of the municipalities of Wiwili and Bocay in the last 40 years were analyzed, the sources were obtained through five years of intense archaeological, historical, linguistic, anthropological and sociological study in the department of Jinotega. We worked with historical documentation of the mentioned municipalities, the ethnographic and ethnological methods and techniques were implemented to record the testimonies of community leaders who were part of the counterrevolution and the Popular Sandinista Army (1981-1990). Likewise, I will discuss the neoliberal agrarian counter-reform of (1990-2006), such as those carried out during the government of Daniel Ortega Saavedra (2007-2019), the latter well accepted by a large part of the peasants on the agricultural frontier in northern Jinotega, who continue to demand more land, at the cost of the displacement and invasion of the indigenous territories of the Mayangnas and Miskitus.